Design and construction of phase change solar thermal accumulator for a family solar dryer: Collaboration with the XXIII Peruvian Symposium on Solar Energy - Janampa Quispe, Kléber (2020)
A solar thermal accumulator is designed and built using the phase change principle, to optimize the drying process in a familiar solar dryer, in an additional period to the cessation of the incidence of solar radiation; the phase change material selected is the commercial paraffin, whose thermal properties have been characterized by the KD2 Pro meter. The melting temperature of the paraffin (53 oC) is around the operating temperature of the medium temperature solar dryer. The solar thermal accumulator is characterized by being modular, consisting of twelve cylindrical units of recycled aluminum, where each unit contains 200 g of paraffin and incorporates meshes with aluminum fins to improve the flow of heat to the outside and optimize its transfer to the air. As a result, the additional drying time has been increased by an order of 2 hours without intervention of solar radiation, maintaining an air temperature greater than 30 °C previously subjected to an average solar radiation of 533 Wm-2.